Circular Economy in Civil Engineering: The Role of Recycled Construction Materials in Economic and Sustainability Performance - Shirin Saiyed (Advanced Business Journal, 2025)
The construction sector plays a vital role in national economic development yet remains one of the highest contributors to resource depletion and carbon emissions. As urbanization accelerates, construction and demolition (C&D) waste presents significant financial, managerial, and environmental challenges. This study provides a comprehensive survey on the economic feasibility, sustainability accounting, strategic management, and Islamic finance perspectives of integrating recycled materials in civil engineering, particularly recycled concrete aggregates (RCA), waste plastics, recycled rubber, glass, and industrial by-products such as fly ash and GGBS. Evidence shows that the adoption of recycled materials contributes to cost efficiency, enhances resource productivity, and supports sustainability reporting through reduced embodied carbon and waste externalities. Management frameworks highlight the role of circular economy models and supply chain integration in improving operational performance. From an Islamic finance viewpoint, recycling practices align with Maqasid Al-Shariah, emphasizing environmental stewardship, avoidance of waste (israf), and promotion of socially responsible investments (SRI). Recent life-cycle assessments by Das, Rahman, and Hossain (2025) demonstrate that incorporating waste-derived materials not only minimizes carbon emissions but also enhances long-term economic value creation. Overall, this study shows that recycled-material innovations in civil engineering strengthen environmental governance, reduce lifecycle costs, and support global sustainability goals, making them highly relevant for policymakers, construction firms, and Islamic financial institutions.